Desmineralização subsuperficial e resistência à fratura do esmalte no desgaste dentário erosivo extrínseco - Nascimento, Johnatan Meireles do (2022)
Currently, the characteristic outcomes of erosive enamel wear (surface demineralization and volume loss) are based on events restricted to the enamel surface, although this tissue presents nanochannels with dimensions that would allow the diffusion of acid molecules to deep parts of the tissue and thus lead to deep subsurface demineralization (SSD) as an outcome. The aim of the present study was to investigate the occurrence of SSD in dental enamel in extrinsic dental erosion and its influence on the fracture resistance. For this purpose, enamel blocks (4 x 4 mm; n = 10), made from human mandibular 3rd molars of subjects aged 17 to 23 years, standardized for surface mineral concentration measured by X-ray microtomography (microCT), were subjected to cycles of erosive wear challenge with 1% citric acid and artificial saliva with mucin for 5 days, with the surface divided into experimental (exposed to acid) and control (protected with acid-resistant wax) parts, forming paired groups. Specimens were analyzed by optical profilometry, quantifying volume loss (stop height); microCT, quantifying lesion depth and ΔΔZ (μm X loss of mineral concentration, before and after erosive challenge); digital radiomicrography, quantifying mineral volume loss; and microdurometer together with fracture line extension measurement, quantifying fracture resistance. The profileometric analyses (n = 10) showed a mean height loss of 7.29 μm (±4.1 μm). Mean lesion depth of 835.39m (±489.39μm) was observed, and a higher ΔΔZ in lesion area (p<0.05; Hedge G-effect magnitude -0.95; 95% CI -0.03/-1.88; power > 82%). Mineral volume loss averaged 2.1% (± 0.8%). The erosion area also showed lower fracture resistance (p < 0.05; Hedge G-effect magnitude 2.92; 95% CI 5.31/0.53; power > 98%). It can be concluded, that the observed evidence suggests that SSD in enamel affected by extrinsic dental erosion presented much deeper than that currently believed, in addition to a lower fracture resistance.